Field evaluation of a semi-automatic funnel trap targeted the medically important non-biting flies - Klong-klaew T. (2017)
© 2017 Elsevier B.V. Bait-trapping is a useful approach for monitoring fly population dynamics, and it is an effective tool for physical control of pest species. The aim of this study was to test a newly developed semi-automatic funnel fly trap with some modifications of the former prototype fly trap to study medically important fly population density. The efficacy of the semi-automatic funnel trap was assessed by field sampling during July 2013-June 2014 using 1-day tainted beef offal as bait. The modified semi-automatic funnel traps were able to capture a total of 151,141 adult flies, belonging to the families: Calliphoridae (n = 147,248; 97.4%), Muscidae (n = 3,124; 2.1%) and Sarcophagidae (n = 769; 0.5%), which are the medically important fly species. Among the total of 35 species collected, Chrysomya megacephala (Diptera: Calliphoridae) (n = 88,273; 59.95%), Musca domestica (Diptera: Muscidae) (n = 1,324; 42.38%) and Boettcherisca peregrina (Diptera: Sarcophagidae) (n = 68; 33.01%) were the predominant species of each family. High number of flies was captured in forest area, representing 42.47% (n = 64,197) of total specimens. Female flies were trapped more than male with total sex ratio of 0.37 male/female. Flies were trapped throughout the year with peak population in summer. Peak activity was recorded in the afternoon (12.00–18.00 h). In summary, the modified semi-automatic funnel fly trap can be used for field collection of the adult fly. By setting the timer, population dynamics, diversity, and periodic activity of adult flies were determined.